Understanding the function of ABCA7 in Alzheimer's disease. (9th October 2015) - Li, Hongyun; Karl, Tim; Garner, Brett
Abstract : ATP-binding cassette transporter A7 (ABCA7) is highly expressed in the brain. Recent genome-wide association studies (GWAS) identify ABCA7 single nt polymorphisms (SNPs) that increase Alzheimer's disease (AD) risk. It is now important to understand the true function of ABCA7 in the AD context. We have begun to address this using in vitro and in vivo AD models. Our initial studies showed that transient overexpression of ABCA7 in Chinese hamster ovary cells stably expressing human amyloid precursor protein (APP) resulted in an approximate 50% inhibition in the production of the AD-related amyloid-β (Aβ) peptide as compared with mock-transfected cells. This increased ABCA7 expression was also associated with alterations in other markers of APP processing and an accumulation of cellular APP. To probe for a function of ABCA7 in vivo, we crossed Abca7 −/− mice with J20 mice, an amyloidogenic transgenic AD mouse model [B6.Cg-Tg(PDGFB-APPSwInd)20Lms/J] expressing a mutant form of human APP bearing both the Swedish (K670N/M671L) and Indiana (V717F) familial AD mutations. We found that ABCA7 loss doubled insoluble Aβ levels and amyloid plaques in the brain. This did not appear to be related to changes in APP processing (C-terminal fragment analysis), which led us to assess other mechanism by which ABCA7 may modulate Aβ homoeostasis. As we have shown that microglia express high levels of ABCA7, we examined a role for ABCA7 in the phagocytic clearance of Aβ. Our data indicated that the capacity for bone marrow-derived macrophages derived from Abca7 −/− mice to phagocytose Aβ was reduced by 51% compared with wild-type (WT) mice. This suggests ABCA7 plays a role in the regulation of Aβ homoeostasis in the brain and that this may be related to Aβ clearance by microglia.